Perancangan Sistem Informasi Penerimaan Siswa Baru berbasis Web (Studi Kasus: SLB Muhammadiyah Golokan Kecamatan Sidayu) - Aji, Galih Wasito; Chotijah, Umi (Jurnal Teknologi Terpadu, 2022)
The admission system for new students in special schools, for example, SLB Muhammadiyah Golokan, is still carried out in a general way, where every prospective student and student's guardian needs to come directly to SLB Muhammadiyah Golokan to fill out the registration form. Admission of new students using this manual method makes it difficult for prospective students because it is less efficient, the long process, and the transportation costs are high, especially for special schools, not as much as public schools. From these problems, the authors create an online website-based information system for new student admissions to make it easier for prospective students and guardians to carry out the registration process. This student admission information system has several features: filling out registration forms, uploading data, validating data, and final reports. The method applied to the development of this system is the Waterfall method. The author uses the PHP programming language and chooses MySQL, which is used for the system database. The results of this study are a new student admissions information system based on an online website that makes it easier for student guardians to register their children at SLB Muhammadiyah Golokan without the need to attend directly school.